Analysis of Generic Skills, Circumstances, Labor Market and Perceived Employability - Joshi, Surendra Prasad; Karki, Dipendra; Ghimire, Binod; Subedi, Sugam (Journal of Interdisciplinary Studies, 2024)
Practical educational and human resource development strategies must maximize the relationship between skill development and employability outcomes. This research examined the relationship between external labor market, university brand, curriculum, emotional quotient, teamwork, and entrepreneurial skills with the student’s perceived employability. This study used a quantitative approach, descriptive research design, and a primary questionnaire method, along with collected 384 responses from college students. To determine sample non-probability convenience sampling used in the study. The study conducted regression, correlation analyses, and descriptive statistics to analyze the data. The findings show a positive relationship between SPE and factors like curriculum, university brand, entrepreneurial skill, emotional quotient, teamwork, and external labor market conditions. Importantly, the quality of the curriculum and the university brand were found to be fundamental determinants of how employable graduates felt about themselves. The study recommends increasing graduates’ employability by strengthening institutional reputation, encouraging entrepreneurial skills, and improving curriculum relevance. These observations add to the quantity of information on employability and provide helpful advice for academic institutions and policymakers who want to match curricula to industry needs better. Future researchers can examine the long-term effects of these traits and determine how applicable they are in different geographic and cultural perspectives.